Determinan Produktivitas Sosial Perbankan Syariah di Indonesia: Two-Stage Malmquist Productivity Index - Julia Maya Pitaloka; Nur Cholis; Azizatul Islamiyah; Zulfikar Bagus Pambuko (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
Islamic banks are obliged to fund and finance the funds to the public. Moreover, Islamic banks are also required to perform social functions. The study aims to analyse the level of social productivity of Islamic Banks in Indonesia and the determinants of it. The data analysis used the Two-Stage Malmquist Productivity Index technique where the first phase uses Malmquist Productivity Index (MPI) and the second uses pooled Tobit regression which applied to 8 BUS from 2013 through 2017. The input variables are the receipt of zakat funds and the charity funds, while the output variables are the use of zakat funds and the charity funds. The results of this study found that Islamic banking has increased productivity in managing social funds by 33.2% where BJB Syariah became the most productive and BRI Syariah is the lowest.Furthermore, the productivity of Islamic Banks in managing social funds is positivelyinfluenced by Return on Assets (ROA) and negatively influenced by the ownership ofindependent LAZ and Capital Adequacy Ratio (CAR), while Financing to Deposit Ratio(FDR) and bank size have no real effect on the social productivity of Islamic Banks inIndonesia.